2004
DOI: 10.1111/j.1600-051x.2004.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative antiplaque and antigingivitis effectiveness of a chlorhexidine and an essential oil mouthrinse: 6‐month clinical trial

Abstract: This 6-month controlled clinical study demonstrated that the essential oil mouthrinse and the chlorhexidine mouthrinse had comparable antiplaque and antigingivitis activity. Insofar as side effects associated with the chlorhexidine mouthrinse may limit patient compliance, it is suggested that each product can have a distinct role in the management of patients with periodontal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
128
3
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(172 citation statements)
references
References 24 publications
21
128
3
10
Order By: Relevance
“…This data confirmed that rinsing regularly with an EOcontaining mouthrinse twice a day can reduce the level of blood-borne bacteria caused by a standardized challenge such as that of chewing an apple. It seems reasonable to assume that maintaining good oral hygiene practices, including tooth brushing, flossing and using an effective antimicrobial mouthrinse agent regularly, contributes to preventing periodontal disease, [7][8][9][10][11][12] which, in turn, leads to a lower risk of developing bacteremia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This data confirmed that rinsing regularly with an EOcontaining mouthrinse twice a day can reduce the level of blood-borne bacteria caused by a standardized challenge such as that of chewing an apple. It seems reasonable to assume that maintaining good oral hygiene practices, including tooth brushing, flossing and using an effective antimicrobial mouthrinse agent regularly, contributes to preventing periodontal disease, [7][8][9][10][11][12] which, in turn, leads to a lower risk of developing bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Essential-oil-containing mouthrinses (EOM) have shown anti-plaque and anti-gingivitis properties in short-7-9 and long-term clinical studies [10][11][12] designed according to the guidelines of the American Dental Association Council on Scientific Affairs. 13 Recently, Fine et al…”
Section: Introductionmentioning
confidence: 99%
“…For example, the active ingredient chlorhexidine attacks and reduces dental biofilm in order to control plaque and gingivitis in the oral cavity [164]. The biofilm is reduced when the individual bacteria walls rupture, as illustrated in figure 16 (www.jjdentalprofessional.com).…”
Section: (I) Cleaning and Disinfectingmentioning
confidence: 99%
“…Por todo esto, se ha considerado a la clorhexidina como un antiséptico tópico ideal debido a su persistente actividad sobre la piel con el uso continuo, un efecto muy rápido y una míni-ma absorción. 17 De esta manera, ante el panorama descrito por múltiples publicaciones que evidencian la asociación entre la aparatología ortodóncica y el incre-…”
unclassified